MENEMUKAN TEOLOGI LOKAL JEMAAT TENTANG COVID 19 : Studi di Jemaat GKE Sion Katunun Kalimantan Selatan - Alexandra Binti; May Linda Sari; Retni Mulyani; Sri Winda Yanti (Unit Penerbitan Informasi dan Teknologi Sekolah Tinggi Teologi Gereja Kalimantan Evangelis (STT GKE), 2022)
This article is based on research that describes the perspectives of Sion Katunun, one of the congregations in the region of Tanah Laut, south of Kalimantan, on COVID 19. How do they relate pandemics to faith and their daily lives? Katunun Congregation is unique because its members are from Java, who came because of the transmigration program in the 1970s. Research conducted in August–December 2021 resulted in five findings: Firstly, the congregation understood COVID-19 as fulfilling biblical statements. Even the practice of self-isolation is like humans entering the ark in the time of Noah. Secondly, knowledge of herbs is a form of local wisdom that can reduce fears and concerns about COVID 19. Thirdly, thru COVID-19, the congregation found a new dimension in the meaning of worshiping God. Fourthly, COVID 19 teaches about solidarity; and lastly, COVID 19 strengthens the relationality in the congregation. The research applied a mixing method and used a descriptive approach. The leading theory applies to the ten positions of the theology of C.S. Song and other theologies of COVID-19 by Joas Adiprasetya and A.A. Yewangoe.